A soluble molecular variant of the semiconducting silicondiselenide1. Issue 9 (10th September 2015) - Chandra Mondal, Kartik; Roy, Sudipta; Dittrich, Birger; Maity, Bholanath; Dutta, Sayan; Koley, Debasis; Vasa, Suresh Kumar; Linser, Rasmus; Dechert, Sebastian; Roesky, Herbert W.
<x xml:space="preserve">Abstract</x> Silicondiselenide is a semiconductor and exists as an insoluble polymer (SiSe2)n which is prepared by reacting elemental silicon with selenium powder in the temperature range of 400–850 °C.